A Low-pressure CO2 adsorption technology using electrospun ABS fiber matrix impregnated with activated local zeolite for potential application to biogas cleaning - Calderon, Aldrin D. (College of Engineering, University of the Philippines Diliman, 2015)
In this study, a novel carbon dioxide adsorption technology was developed using electrospun mixed matrix membrane with activated zeolite. Natural local zeolite was modified to improve Na+ uptake and was found to increase Na+ up to 5.46% isomg EDS. Structural characterization was performed for the activated zeolite framework using XRD. Meanwhile, FTIR spectra showed domination by the absorption of zeolite in ABS as vibrational stretching on 1039 cm-1 appears on ABS-zeolite composite attributed to SiO2 zeolitic phase as zeolite phase of OH- bending mode on wavenumber 1636 cm-1 disappeared. The disappearance of this dominant peak, formation of new intense absorption bands and stretch on triple band area proved conformational changes in macromolecules of ABS as zeolite was dispersed. The 5 wt % modified zeolite-filled electrospun fibers collected at 30 kV using 80 cm2 aluminum mini-collector plates with the distance of 17 cm showed more porous fibers produced with thinner diameter compared to other collector methods as confirmed by SEM. The development of porous fibers was preferred to produce a multiple pore system for gas separation: (a) pores between fibers, (b) pores on fiber surface and (c) pores on zeolite. A gas separation set-up was established to simulate low-pressure CO2 adsorption in small scale biogas system. Using GC, was analysis on permeate gas shows that 5 wt % zeolite-filled membrane obtained a retention factor of 37.8% which was the highest compared to sodalite-filled membrane and commercially available gas purifier. Results were analysed using RSM and it was found that the CO2/CH4 mixed gas composition was the most significant factor that influenced CO2 adsorption followed by the amount of adsorbent. Lastly, AHP was used to check the viability of the novel CO2 adsorption technology and to identified the ranking of criteria and alternatives. Prioritization of criteria with the relative weights is as follows: economical 40%, environmental 33%, social 19% and technical 8%. Rankings of criteria were all consistent and reliable based on consistency check performed. The alternatives used were also ranked with electrospun fibrous membrane gaining the highest relative prioritized weights of 30.4% showing the viability of the purification technology for small scale low-pressured biogas plant.